Penguatan Sinergitas Antara Badan Narkotika Nasional Kabupaten Pelalawan Dengan Pemerintah Kecamatan Pangkalan Kerinci Dalam Pemberantasan NARKOTIKA - Hakim, Arif Rahman; Rio Tutrianto; Rendi Tri Afrianda; Nova Risma; Anggi Tri Murni; Roudhoh Firdana (Journal Of Rural Community Development, 2026)
Drug abuse and illicit trafficking are serious problems that require the integrated involvement of various parties. This community service activity aims to strengthen the synergy between the National Narcotics Agency (BNN) of Pelalawan Regency and The Pangkalan Kerinci District Government in efforts to eradicate narcotics. The implementation method includes socialization of the dangers of narcotics, cross-sector coordination, capacity building of sub-district officials, and community involvement in drug abuse prevention and eradication programs. The results of the activity indicate an increase in understanding of government officials and the community regarding their respective roles in the Prevention, Eradication, Abuse and Illicit Trafficking of Narcotics (P4GN). In addition, more effective communication and cooperation were established between the BNN of Pelalawan Regency and the Pangkalan Kerinci District Government. This activity is expected to become a model of sustainable collaboration in creating a community environment free from narcotics..